The Citrus Flavanone Hesperetin Induces Apoptosis in CTCL Cells via STAT3/Notch1/NFΚB-Mediated Signaling Axis - Kottaiswamy, Amuthavalli; Kizhakeyil, Atish; Padmanaban, Abirami M.; Mirza, Fathima B.; Vijay, Venkatesh R.; Lee, Pin S.; Verma, Navin K.; Kalaiselvan, Parkavi; Samuel, Shila (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Hesperetin is a natural compound known for its cholesterol-lowering effect and a wide range of pharmacological activities. Objectives: Investigating the potential anticancer activities of Hesperetin in malignant hematolymphoid cell lines HuT78 and MJ, derived from patients with Cutaneous T-Cell Lymphomas (CTCL). Methods: The cytotoxic effect of Hesperetin on two different CTCL cell lines, HuT78 and MJ, was assessed by MTS-based colorimetric assay. Apoptosis, cell cycle, ROS (Reactive Oxygen Species) and molecular analysis were performed using flow-cytometry and immunoblotting. Results: Hesperetin-treated CTCL cells were arrested at the sub-G1 phase of cell cycle with the concomitant decrease in the expression of the cell cycle regulator protein cyclin B. In addition, the study found that the cellular treatment with Hesperetin caused an induction of apoptosis, which was independent of ROS generation. Hesperetin caused a significant decrease in the expression level of anti-apoptotic protein Bcl-xL and an increase in cleaved caspase-3 and PARP proteins in CTCL cells. Furthermore, Hesperetin treatment in CTCL cells down-regulated the expression of Notch1 and phosphorylation of STAT3 (Tyr705) and inhibited NFΚBp65. Conclusion: This study highlights the anticancer properties of Hesperetin. Which induces apoptosis in CTCL cells via STAT3/Notch1/NFΚB mediated signaling pathway, suggesting that further development of this novel class of flavonoid may contribute to new drug discovery for certain hematolymphoid malignancies.
Keywords: ROS